Hydroxiapatite (HAp) Bioceramics Made from The Caletaiya presclupta Snail Shells from Poso Lake - Agung Rimayanto Gintu; Elisabeth Betty Elok Kristiani; Yohanes Martono (JKPK (Jurnal Kimia dan Pendidikan Kimia), 2020)
Bioceramic Hydroxyapatite (HAp) was a derivated chemical synthetic compound from calcium phosphate commonly used to care for hard tissue damage. Bioceramic Hydroxyapatite can be synthesized from the compounds rich with calcium contains. This study treated the synthesis and physicochemical Characterization of the HAp made from Celetaiya persclupta snail shells obtained from Poso lake. From the characterization of the sample C. presclupta shells obtained the water contains 0.50±0.00%; ash contains 0.9913±0.0017g/g; potassium 0.0005±0.00007g/g; calcium 0.0391±0.0059g/g; phosphate 0.0221±0.0009g/g; phosphorus 0.0111±0.0005  and the ratio of  Ca/P 1.7382±0.1994%. The synthesis of HAp by base precipitation method showed the yield of synthesis 85.2891±4.2496% with the level of material reduction during synthesis 18.0442±1.1684%. The result of characterization of the HAp showed that the potassium contains 0.0002±0.00003g/g; calcium 0.0121±0.0031g/g; phosphate 0.0167±0.0013g/g; phosphorus 0.0084±0.0007g/g; ratio of Ca/P 1.3724±0.2736%; porosity 9.9929±0.7626%; swelling ability 24.8416±1.4989%; and biodegradability 10.8958±1.1781%. The overall results concluded that the C. presclupta snail shells could become a source of Bioceramic Hydroxyapatite (HAp).